A relay-based hybrid PSO-jaya algorithm for efficient test redundancy reduction - Mojumder, Md Anis; Kamal Zuhairi, Zamli; Kader, Md. Abdul; Qasymeh, Montasir; Mistarihi, Mahmoud (IEEE, 2026)
In software development, test redundancy increases resource consumption and execution time. To address this problem, Test Redundancy Reduction (TRR) has emerged as a critical optimization problem in software testing. In this context, we introduce a Relay-based Hybrid PSO-Jaya algorithm, which employs PSO for its strong global exploration capability, followed by Jaya to perform local refinement of promising regions in the search space. This sequential relay allows PSO to broadly explore the solution space while Jaya intensifies the search around highquality candidates. Experimental results across four benchmark datasets show that the proposed relay-based hybrid approach consistently outperforms standalone PSO and Jaya in terms of test reduction percentage and full requirement coverage. Furthermore, the effect of the algorithmic sequence (PSO-Jaya vs. Jaya-PSO) is also evaluated, highlighting the importance of strategic hybridization order. The findings demonstrate that the proposed relay-based hybrid metaheuristics offer a promising direction for addressing TRR in large-scale test suites.